PENGGUNAAN MEDIA PERMAINAN UNO STACKO UNTUK PENGUASAAN KOSAKATA DALAM PEMBELAJARAN BAHASA JEPANG LEVEL DASAR - AINIS SYIFA, DINA (HIKARI, 2020)
?? ??????????1???????????????????????????????????2????????3????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????1????????? 2????????????????????????? 3????????????????????????????????? 4????????????????????????????????????????????????????????????????????????????????????????? ?????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????? ???????????????????????????? Abstract The purpose of this study are: 1) describe the steps in the application of Japanese vocabulary learning using Uno Stacko media, 2) describe the advantages and 3) describe the weaknesses of Uno Stacko game media when applied in Japanese learning. The method used in this research is library research. Data collection techniques used in this study are documentation techniques with the study of literature that is gathering information from a variety of reference sources in the form of scientific literature relating the variables in this study. Data analysis techniques using secondary data analysis methods through the results of previous research in the form of theses, articles, and papers based on the theme of this study. The results of this study can be seen that the application of learning by using Uno Stacko Japanese vocabulary media games is done with the following short steps: 1) Division of groups. 2) Explanation of the rules and how to play Uno Stacko game media. 3) Students start doing learning activities according to the rules of the game and instructions from the teacher. 4) The teacher as a time controller and student activities so that the activities run according to the learning scenario and students remain conducive to follow the course of activities properly and correctly. The advantages of Uno Stacko game media are that it can increase student motivation, improve students cognitive abilities or knowledge, encourage students to be more active in learning activities, and improve social skills. While the weaknesses they have are that the classroom atmosphere is poorly controlled, the making of it consumes a considerable amount of time, energy, and cost, and allows students to become less focused with the learning objectives. Keywords: learning media, Uno Stacko game, vocabulary mastery